CRITICAL ANALYSIS OF RIGHT TO ABORTION OF MOTHER VIS-A-VIS RIGHT TO LIFE OF AN UNBORN CHILD - Dr Maryam Ishrat Beg, Ms Monika Punia (International Journal of Advanced Science and Technology, 2020)
Basic human rights can only be enjoyed when the human right to life is protected, and this right should be protected not from the moment of birth but from the moment a child is conceived. Though giving such importance to the right to life of an unborn child is a threat to the reproductive rights of women. So now the question before us to decide remains is whether the right of a fetus should supersede the mother’s right to exercise her right to autonomy? As a human being, a woman has all the right to freely choose and decide everything regarding their personal and professional life and this wide umbrella of rights covers the right to autonomy, which includes a woman’s choice to make a sound decision regarding marriage, having children and with whom to have children.